Meningkatkan Kualitas Pembelajaran Melalui Supervisi Bersahabat Pada Guru SD Negeri 024763 Binjai Tahun Pelajaran 2018/2019 - Lisprija Lisprija (Keguruan, 2022)
This study aimed to find out how the role of friendly supervision can improve the quality of learning and how the teacher's creativity and ability in carrying out the learning in classroom. The hypothesis is: How to improve the quality of learning and the ability of teachers to carry out learning that can be improved through friendly supervision. School action research was carried out in two cycles by using the model developed by Kurt Lewin that consisted of four components, namely: planning, action, observation and reflection. The results of this study concluded that the teacher's ability to implement the learning model before friendly supervision was carried out in the sufficient category as 6o%;  after the action was carried out in the cycle, the teacher's discipline level as 70% increased to 90% in cycle II.  Then in cycle I, the percentage of teachers who  completed learning tools by 80% increased to 90% in cycle II, and in cycle I, the percentage of teachers who taught by using new learning methods/models increased from 80% to 100% in cycle II.